Phylogeography between valleys and mountains: The history of populations of Liolaemus koslowskyi (Squamata, Liolaemini) - Morando, Mariana (2008)
The lizard genus Liolaemus is endemic to temperate South America and includes approximately 200 species. Liolaemus koslowskyi occurs in north-western Argentina, where it is confined to a system of interior basins and valleys. This topographically complex region is now viewed as different enough that it has been suggested for recognition as a separate zoogeographical region: The Monte Desert of Mountains and Isolated Valleys. Here we use the mtDNA cytochrome b sequence data to investigate the phylogeographical pattern of L. koslowskyi and its relationships with other species of the darwinii group. Liolaemus koslowskyi is monophyletic with respect to all the species of the darwinii group included in this analysis. Three main clades were recovered within L. koslowskyi and we hypothesized that at least one of these, which shows 7% genetic divergence, is a candidate species. We discuss the phylogeographical patterns in association with the geological history of the region. The highly structured L. koslowskyi clade suggests that it has a relatively ancient history in a topographically rich, terrestrial archipelago of habitat and tectonic islands that are themselves relictual mountains and valleys.